1995
DOI: 10.1017/s0003598x00082363
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary change in the mountains of New Guinea

Abstract: At the south and north limits of our region are mountainous areas very different from the open arid spaces of the Australian continent between. In the north, the high country of New Guinea offers a complex and well-studied environmental sequence as the arena for early and puzzling human adaptations, precursor of the extraordinary societies of the island today.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…The Physical Environment, Landscape Evolution and Resource Availability 29 terra australis 38 bottom sediment data from sites in Australian and the circum-Paci c region (McPhail and Hope 1985;Brook eld and Allan 1989;Singh and Luly 1991;McGlone et al 1992;Hope and Golson 1995;Kershaw 1995;Shulmeister and Lees 1995;Nott et al 1999:233;Rodbell et al 1999;McCarthy and Head 2001;Kim et al 2002;Koutavas et al 2002). Geomorphic evidence from cheniers and coastal dune elds (Lees et al 1990(Lees et al , 1992Lees 1992aLees , 1992b indicates that some of the observed changes in these systems are synchronous across north Australia, and may represent coherent, broad-scale climatic signals (Shulmeister 1999:82;Prebble et al 2005:367-9).…”
Section: Climatic Change During the Holocenementioning
confidence: 99%
“…The Physical Environment, Landscape Evolution and Resource Availability 29 terra australis 38 bottom sediment data from sites in Australian and the circum-Paci c region (McPhail and Hope 1985;Brook eld and Allan 1989;Singh and Luly 1991;McGlone et al 1992;Hope and Golson 1995;Kershaw 1995;Shulmeister and Lees 1995;Nott et al 1999:233;Rodbell et al 1999;McCarthy and Head 2001;Kim et al 2002;Koutavas et al 2002). Geomorphic evidence from cheniers and coastal dune elds (Lees et al 1990(Lees et al , 1992Lees 1992aLees , 1992b indicates that some of the observed changes in these systems are synchronous across north Australia, and may represent coherent, broad-scale climatic signals (Shulmeister 1999:82;Prebble et al 2005:367-9).…”
Section: Climatic Change During the Holocenementioning
confidence: 99%
“…A pollen record from Groote Eylandt indicates a marked decline in precipitation between 4,000 and 3,500 BP, with increased rainfall during the last thousand years (Schulmeister and Lees 1992). These general trends toward increased aridity in the mid-Holocene are supported by records of flood deposits in the Kimberley (Gillieson et al 1991) and by other indicators such as ÎŽ 18 O records extracted from coral, foraminifera, varve, lake and sea bottom sediments from sites in Australian and the circum-Pacific region (Brookfield and Allan 1989;Hope and Golson 1995;Kershaw 1995;Koutavas et al 2002;McCarthy and Head 2001;McGlone et al 1992;McPhail and Hope 1985;Rodbell et al 1999;Singh and Luly 1991).…”
Section: Climate Changementioning
confidence: 84%
“…several wetland sites in the highlands of New Guinea: Denham et al 2003;Powell 1970) and off-site (e.g. Kosipe : Hope 1982;Hope and Golson 1995) applications. The presence and proportion of diagnostic vegetation communities have been identified, including secondary growth, anthropogenic grasslands and weedy species (Haberle 1994), as well as economically significant plants (e.g.…”
Section: Microfossilsmentioning
confidence: 99%